Opportunities and Challenges Facing the Development of the Management Control Systems Package - Angelova, Antoaneta (Research Papers, 2023)
This article presents the opportunities and challenges facing the development of the management control systems package. There is an analytical review of the scientific literature. This review includes the nature and characteristics of management control systems and these systems package, their place and their role in the organization. The analytical review comprises index publications in global databases such as ACM Digital Library, Elsevier, Scopus and Google Scholar. The toolkit covers induction and deduction methods, including analysis, synthesis and summaries. The results of the review of the management control systems concepts give grounds for concluding that these systems need modernizing by integrating additional elements into their composition. The following are the main directions of modernization and expansion: the monitoring of various psychological aspects of the employee, the construction of permanent communication channels and the development of a methodology for managing management control systems package.